Disappearance of the Polar Cap Ionosphere During Geomagnetic Storm on 11 May 2019 - H.‐J. Kwon; K.‐H. Kim; G. Jee; J. Seon; C. Lee; Y.‐B. Ham; J. Hong; E. Kim; T. Bullett; H.‐U. Auster; W. Magnes; S. Kraft (Space Weather)
Abstract Multi‐instrument data from Jang Bogo Station (JBS) in Antarctica were utilized to study ionospheric responses to the 11 May 2019 moderate geomagnetic storm. These include Vertical Incident Pulsed Ionospheric Radar (VIPIR)/Dynasonde, Fabry‐Perot Interferometer (FPI), GPS vertical total electron content (vTEC), and magnetometer. The VIPIR/Dynasonde observed long‐lasting (>11 hr) severe depletion of the electron density in the F‐region ionosphere over JBS. During the depletion interval, GPS TEC also correspondingly decreased, FPI neutral temperature was significantly enhanced, and the polar magnetic field variations showed positive and negative excursions in the Y (east) and Z (vertical) components, respectively. GK‐2 A satellite, located ∼2.5 hr west of JBS, observed negative magnetic field perturbations in the azimuthal BD component at geosynchronous orbit during the depletion of ionospheric plasma. Such a BD perturbation at geosynchronous orbit is due to the field‐aligned currents flowing out of the ionosphere. From these observations we suggest that transpolar ionospheric currents connected to the field‐aligned currents flowing on a substorm wedge‐shaped circuit act as a source of polar atmospheric heating during the moderate geomagnetic storm interval and that elevated heavy molecular gases (O2 and N2) by atmospheric heating contribute to the electron density depletion via increased recombination rate.